Case Report: Unraveling clinical heterogeneity in DEPDC5-related epilepsy: a genotype–phenotype correlation study in eight pediatric cases - Zhao, Tong; Chen, Fang; Cao, Bin; Yang, Liqun; Yin, Jiaqi; Li, Yanqi; Feng, Fan (Frontiers in Neuroscience, 2025)
ObjectiveTo summarize the clinical characteristics of eight children with DEPDC5 gene variant-associated epilepsy.MethodsClinical data of children with DEPDC5-related epilepsy treated at Hebei Provincial Children’s Hospital from April 2020 to November 2024 were retrospectively analyzed.ResultsAmong the 8 children (5 males, 3 females), age of onset ranged from 1 year 4 months to 9 years 3 months. Genetic analysis revealed 6 missense mutations, 1 code-shift mutation, and 1 large segment deletion, including 1 de novo and 7 hereditary mutations. Four children exhibited global developmental delay. Seizure types included generalized tonic–clonic (5 cases), tonic (1 case), and 2 forms of seizures: tonic seizures and atonic seizures (2 cases). EEG showed abnormal discharges in all cases: focal (4 cases), multifocal (3 cases), and slow-wave (1 case). Brain MRI abnormalities were observed in 4 children, including delayed myelination, hyaloid septal cavities, and microgyrus malformation. Diagnoses included Lennox–Gastaut syndrome (4 cases) and self-limiting epilepsy with centrotemporal spikes (2 cases). Six children responded well to medication (seizure reduction >25%), while 2 had poor control.ConclusionDEPDC5 gene mutations result in diverse phenotypes, potentially influenced by age of onset and mutation type. Generalized seizures were most common, with high rates of EEG abnormalities and structural brain changes. In a few cases (3 cases), treatment with levetiracetam and phenobarbital can reduce the frequency of epileptic seizures by 25%, but due to limited sample size, its exact efficacy still needs further research and verification.